Comparative evaluation of low-dose levobupivacaine and ropivacaine in patients undergoing inguinal herniorrhaphy under walking spinal anaesthesia as daycare surgery - Singh, Priyanka; Kapur, Anu; Gupta, Sanjay Kumar (Bali Journal of Anesthesiology, 2019)
Background: Ropivacaine and levobupivacaine possess the property of sensory-motor dissociation. Hence these drugs allow a faster recovery of motor function and hence, these are potentially useful agents for walking spinal anaesthesia in daycare surgeries.Patients and Methods: This is a prospective, double-blind, randomized study involving 120 adult ASA 1 and 2 patients who were randomly allocated into two groups. Group R (n = 60) received 7.5 mg 0.75% ropivacaine + 25 ?g fentanyl + 1.5 ml sterile water. Group L (n = 60) received 5 mg 0.5% levobupivacaine + 25 ?g fentanyl + 1.5 ml sterile water. Each solution was made to a total volume of 3 ml, administered intrathecally. Sensory and motor block characteristics, hemodynamic changes and postoperative recovery profile characteristics were noted. Paired/unpaired t-test and chi-square test were used wherever applicable for statistical analysis using SPSS version 15.0. Results: Sensory block onset time and time to reach the maximal cephalic spread were comparable in both the groups, whereas time to the two-segment regression and time to first analgesic requirement were significantly shorter in group RF. Out of 60 patients in each group, 59 patients in group RF and 57 patients in group LF were MBS grade 5. Time to home discharge was also significantly shorter in group RF.Conclusion: We concluded that both local anaesthetics could be used in the walking spinal technique; however, ropivacaine is preferred because of its favourable block characteristics and early ambulation time.